Pengaruh Literasi Digital Dalam Membangun Citra Diri Dan Kesehatan Mental Remaja Di Era Teknologi - Erin Selita Sirait; Ficry Ramadhani; Valdis Sandya Akhjan (CV. ITTC INDONESIA, 2025)
The rapid advancement of digital technology has significantly influenced adolescents’ social interactions and identity formation. A lack of media ethics awareness, limited digital literacy, and increasing social pressure in digital spaces can negatively affect adolescents’ self-image and mental health. Based on these challenges, this Community Service Program (PKM) was conducted at SMA Negeri 6 Tangerang Selatan to enhance students’ understanding of digital literacy, develop positive self-image, and promote mental well-being in the digital era. The activity employed a qualitative, participatory, and educational approach through interactive lectures, group discussions, case simulations, and reflective sessions. Students served as the primary participants, supported by teachers and educational staff as facilitators. The results indicate a significant increase in students’ awareness of responsible digital behavior, a deeper understanding of the relationship between online activities and self-concept, and improved emotional regulation strategies. Participants also demonstrated a positive shift in using social media—from mere entertainment to a medium for learning and constructive self-expression. Overall, this PKM program effectively fostered critical thinking and digital responsibility among adolescents, providing a practical model for digital character education within schools.